EnviBUILD buildings and environment 2013 : selected, peer reviewed papers from the International Conference on EnviBUILD 2013, Buildings and Environment, October 17, 2013, Bratislava, Slovakia - Maňková, Lucia; Hanuliak, Peter (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the EnviBUILD 2013, Buildings and Environment, October 17, 2013, Bratislava, Slovakia. The 120 papers are grouped as follows: Chapter 1: Energy Efficient Buildings, Chapter 2: Heat Storage and Energy Savings, Chapter 3: Integration of Renewable Energy sources, Chapter 4: Effective Ventilation, Chapter 5: Quality of Indoor Environment, Chapter 6: Natural and Environmental Friendly Building Materials, Chapter 7: Acoustic Design and Noise Protection, Chapter 8: Fire Protection, Risk Analysis, Chapter 9: Information Technologies in Building, Chapte.